Study on Chemical Non-polar Solvent Heating by Microwave - Xu, Chen; Jun, Shu; Yang, Xiaoqing; Huang, Kama; Liu, Pukun (Asian Journal of Chemistry, 2012)
The choice of vessel is vital for heating non-polar solvent. In this paper, non-polar solvent at container with different vessel wall sizes and properties was heated indirectly by microwave. The uniformity of temperature was analyzed using COMSOL multiphysics under different vessel walls during microwave heating. The results show that the temperature uniformity was influenced by the different parameters of vessel wall sizes and properties and the uniformity of temperature can be highly improved by changing the thickness and property of vessel wall.